Popular Dance and Music in Modern Egypt. - Zuhur, Sherifa (McFarland and Company, Inc. : McFarland, 2021)
"Based on multiple decades of research on and experience with Egyptian dance and music, this book is a unique exploration into the history, expansion, aesthetics, social reality, regulation, and transformation of different forms of dance and dance music in Egypt. The book covers raqs sharqi (Oriental dance, known as belly dance or danse du ventre), raqs sha'biyya (regional or group-specific dances and rituals), sha'bi (lower-class urban music and a dance style), mulid (drawing on Sufi tradition and the festive character of saints' day festivals) and mahraganat (youth-created, primarily electronic music with lively rhythms and biting lyrics). Each chapter touches on a different aspect of Egyptian dance, including genres and sub-genres and evolution, the demeanor of dancers, trends old and new, and social and political criticism using the imagery of dance or a dancer. It also considers the globalization of Egyptian dance, the replication or fantasies of raqs sharqi outside of Egypt, as well as the adoption of the dance as a hobby, competitive dance form, and focus of international dance festivals"--